Exploring the evolution and trends of innovative entrepreneurship: a bibliometric analysis - Cano-Vargas, Alvaro Alexander; Osorio-Toro, Carlos Andrés (Clío América, 2024)
Innovative entrepreneurship is highly significant for fostering new opportunities that add value to businesses and society; it is a field of study that necessitates regular monitoring of the state of the art. This paper aims to conduct a bibliometric analysis of innovative entrepreneurship to identify its intellectual structure and research trends, sourcing literature from Scopus and Web of Science (WoS) to conduct a bibliometric analysis. Researchers applied the Tree of Science (ToS) algorithm to discern an intellectual structure by drawing an analogy with roots, trunk, and branches, retrieving 1654 documents from Scopus and 680 from WoS, amounting to 1 795 non-duplicate documents; they observed a growing trend in scientific production, complemented by findings regarding countries, journals, authors, and their collaboration networks. Three significant trends emerged in the analysis using ToS: 1) Strategic Entrepreneurship, Digital Transformation, and Higher Education; 2) Technology as a Keystone in Entrepreneurial Innovation Ecosystems; and 3) Public Policy and Innovation Dynamics in Entrepreneurial Development. Researchers concluded that innovative entrepreneurship remains an inexhaustible field requiring further research development.